Early Detection and Progression of Knee Osteoarthritis Using Advanced Deep Learning and Imaging Techniques - D. Kale, Ravindra; Khandelwal, Sarika (Journal of Neonatal Surgery, 2025)
Osteoarthritis (OA) of the knee is a degenerative joint condition that causes cartilage to break down, resulting in pain, stiffness, and loss of function. Early detection and monitoring of disease progression are crucial for effective treatment. Recent advances in deep learning (DL) and imaging techniques, particularly in medical imaging modalities like MRI, X-rays, and ultrasound, offer promising avenues for early diagnosis and predictive modeling of knee OA progression. This comprehensive study aims to explore state-of-the-art deep learning algorithms applied to various imaging modalities to enhance early detection and track disease progression.